2021
DOI: 10.48550/arxiv.2101.02483
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust Text CAPTCHAs Using Adversarial Examples

Abstract: CAPTCHA (Completely Automated Public Truing test to tell Computers and Humans Apart) is a widely used technology to distinguish real users and automated users such as bots. However, the advance of AI technologies weakens many CAPTCHA tests and can induce security concerns. In this paper, we propose a user-friendly textbased CAPTCHA generation method named Robust Text CAPTCHA (RTC). At the first stage, the foregrounds and backgrounds are constructed with randomly sampled font and background images, which are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…In 2021, a text-based CAPTCHA generation technique named Robust Text CAPTCHA (RTC) is proposed in [16]. The evaluation results showed that the proposed method has a high usability level and robust level against different defensive techniques.…”
Section: Techniques For Generating Adversarial Captchamentioning
confidence: 99%
See 3 more Smart Citations
“…In 2021, a text-based CAPTCHA generation technique named Robust Text CAPTCHA (RTC) is proposed in [16]. The evaluation results showed that the proposed method has a high usability level and robust level against different defensive techniques.…”
Section: Techniques For Generating Adversarial Captchamentioning
confidence: 99%
“…CAPTCHA Scheme Perturbations Domain [3] Image-based Space [14] Image-based Space Text-based [15] Text-based Space [13] Image-based Space Text-based Click-based [4] Text-based Space [5] Image-based Space [18] Text-based Frequency [6] Text-based Space [16] Text-based Frequency [17] Text-image-based Space [18] Image-based Space [37] Audio-based Space [41] Image-based Frequency [38] Audio-based Space…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The work presented in this paper is related to defeating text-CAPTCHA schemes. As they are widely applicable across the internet, both in the commercial and non-commercial sectors [14,30]. Therefore, it is important to continue researching the security strengths of this kind of CAPTCHA scheme and bring awareness of its weaknesses to stakeholders.…”
Section: Related Workmentioning
confidence: 99%